The FT/TFL1 gene family in grapevine - Carmona, María José; Calonje, Myriam (Plant molecular biology, 2006)
The FT/TFL1 gene family encodes proteins with similarity to phosphatidylethanolamine binding proteins which function as flowering promoters and repressors. We show here that the FT/TFL1 gene family in Vitis vinifera is composed of at least five genes. Sequence comparisons with homologous genes identified in other dicot species group them in three major clades, the FT, MFT and TFL1 subfamilies, the latter including three of the Vitis sequences. Gene expression patterns are in agreement with a role of VvFT and VvMFT as flowering promoters; while VvTFL1A, VvTFL1B and VvTFL1C could be associated with vegetative development and maintenance of meristem indetermination. Overexpression of VvFT in transgenic Arabidopsis plants generates early flowering phenotypes similar to those produced by FT supporting a role for this gene in flowering promotion. Overexpression of VvTFL1A does not affect flowering time but the determination of flower meristems, strongly altering inflorescence structure, which is consistent with the biological roles assigned to similar genes in other species.